Credit Driven Investment, Heterogeneous Labor Markets and Macroeconomic Dynamics - Matthieu Charpe; Peter Flaschel; Hans-Martin Krolzig; Christian Proa\~no; Willi Semmler; Daniele Tavani (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
In this paper we set up a baseline, but nevertheless advanced and complete model representing detailed goods market dynamics, heterogeneous labor markets, dual and cross-dual wage-price adjustment processes, as well as counter-cyclical government policies. The cyclical movements of output generate, through Okun's law, employment variations in the heterogeneous labor market. The core of the resulting Keynesian macrodynamics is however given by credit-financed investment behavior and loan-rate setting by credit suppliers. The framework is constructed in such way that simplified, lower dimensional versions of the model can be obtained by setting parameters describing specific feedback effects from one sector to another equal to zero. Starting from such low dimensional sub-dynamics, we show through a ``cascade of stable matrices'' approach that the local stability of the full 7D model is given if the feedback chains are sufficiently tranquil in their transmission mechanisms. However, local stability is the point of departure for the numerical investigation of local explosiveness and the forces that can bound such a behavior.
urn:nbn:de:101:1-201303149672
Keywords: E12; E24; E31; E52; 330; Macroeconomic (In-)Stability; Segmented Labor Markets; Business Cycles; Fiscal and Monetary Policy Rules; Arbeitsmarktsegmentation; Wirtschaftliche Instabilität; Makroökonomik; Konjunktur; Geldpolitik; Okunsches Gesetz